Singer (Malaysia) Sdn. Bhd.: easy payment scheme - Singer's road to success / Zulita Ismail - Ismail, Zulita (1991)
It is a common fact to every marketer that social, political, regulatory, ethical and economic factors can obviously impinge the choice of a marketing strategy in a company. A company's marketing strategy and these factors is a two way street, thus they should focus on how the need for overall societal approval of a firm's behaviour, together with a firm's perceived social and ethical obligations constrain strategy formation. That consumerism truth in packaging, equal concern for environmental protection, nutritional issues, beliefs about ethics and moral, and other similar socital based factors have an impact on organisation's strategies require no discussion. Thus adapting strategy to accomodate these factors is common place. Managerial alertness to the implications of societal forces and political economic concerns is now an essential part of the marketing formulation process.